Dynamic Plastic Energy Absorption in Vehicle Impact - Perrone, N. (Engineering Transactions, 1981)
Simplified as well as comprehensive dynamic plastic mathematical models of vehicle structures can and do play a very useful role for the purpose of assessing energy absorption potential for vehicle or highway structures during impact. A number of success stories are evident within the vehicle itself in the windshield, door latches, and steering columns as well as overall vehicle crush capability. In the highway environment the advent of energy absorbing barrier systems, breakaway sign points, and effective bridge rail systems have contributed noticeably to improved safety on the highway. The awareness by the design community of the effectiveness of improved energy absorption has resulted in improved vehicle safety. With no standard existing or contemplated in the U.S. for vehicle energy absorption, this capability is left largely up to the discretion of the manufacturer. Selective increments in vehicle component energy absorption are feasible (front, rear, side, interior) via static tests with rate sensitivity correction factors and also possibly the use of lumped mass models. The need for energy absorption is tempered with the challenge of decreasing weight of vehicles because of energy saving requirements. This difficulty challenges the ingenuity of the designer but there is likely still much room for improvements when we consider that the specific energy absorption for various configurations can be made quite high [1]. A complicated problem with the Unites States in recent years has been the big car-small car mix. During impacts between vehicles of grossly different weight the smaller car obviously suffers heavily. This transition period makes it even more imperative, to have good impact absorbing capabilities within the very light and small vehicle. In addition, a trend also exists toward lighter weight materials such as the use of composites (which are under study). The energy absorption of these materials must be examined very closely because they frequently would not be as ductile as metals which they are trying to replace. Rate sensitivity for these newer materials are may also still be a problem. The challenge of packaging people in vehicles to survive impact events, not consume too much energy, and still provide the function of reasonable transportation is indeed formidable and is being met very capably by the mechanics, materials, and engineering communities.